Rapid opto-electrochemical differentiation of marine phytoplankton - Yu, J; Yang, M; Batchelor-McAuley, C; Barton, S; Rickaby, R; Bouman, H; Compton, R (American Chemical Society, 2022)
The use of electro-generated oxidants in seawater facilitates the discrimination of different plankton groups via monitoring the decay in real time of their chlorophyll-a (chl-a) fluorescence signals following potentiostatic initiation of electrolysis in their vicinity (Yang, M. Chem. Sci.2019, 10(34), 7988−7993). In this paper, we explore the sensitivity of phytoplankton to different chemical species produced at various potentials in seawater. At low potentials, the oxidation of ca. millimolar bromide naturally present in seawater to hypobromous acid ‘switches-off’ the chl-a signal of individual Chlamydomonas concordia cells (green algae) located on the electrode surface within tens of seconds of the potential onset. At higher oxidative potentials, the oxidation of chloride and water produces oxidants (Cl2, OH, H2O2, etc.) that are also lethal to the plankton. To deconvolute the contributions to the response from the chemical identity of the oxidant and the amount of charge delivered to ‘titrate’ the individual living plankton using the loss of fluorescence as the ‘end point’, we introduce a ramped galvanostatic method. This approach enabled the controlled injection of charge applied to a bespoke electrochemical cell in which the plankton are immobilized on an electrode surface for rapid and sensitive measurement. It is shown that the number of moles (charge) of oxidants required to react leading to chl-a switch-off is independent of the chemical identity of the electro-generated oxidant(s) among hypobromous acid, chlorine, or water-derived oxidants. Comparative experiments between C. concordia and Emiliania huxleyi (where the latter are encapsulated by extracellular plates of calcium carbonate) show that significantly different amounts of absolute charge (moles of electro-generated oxidants) are required in each case to ‘switch-off’ the chl-a signal. The method provides the basis for a tool that could distinguish between different plankton cells within ca. 2 min including the setup time.